The Use of Oral Drill Method in Teaching Speaking Skill - Adib Ahmada; Yeni komariyah (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2022)
English is one of difficulties subject in Indonesia. Therefore, speaking is one of important skills students must master at school. While the eighth grade excellent class of MTs Al-Amiriyyah had problem in speaking, most of them felt difficult to pronounce English. They were also less vocabulary and don't understand English lesson. The aim of this research was to describe the use of oral drill method in teaching speaking at eighth grade excellent class of MTs Al-Amiriyyah in academic year 2020/2021. This research used descriptive qualitative design. This research studied about English teaching method conducted by Mrs. Atiya who was a teacher at eighth grade excellent class of MTs Al-Amiriyyah Blokagung Tegalsari Banyuwangi. This research involved 23 female students as the subject. The researcher used classroom observation, interview, and documentation to collect data. Based on the result of observation, there was improvement of students at eighth grade excellent class of MTs Al-Amiriyyah. From the results of the student's scores, it showed that the students lowest score was 75, the students’ highest score was 95 and the average score was 84.3. Based on the result, the researcher concluded that the oral drill method in teaching speaking was successful for improving speaking ability